Penguatan Karakter Anti Cyberbullying Melalui Video Edukatif Berbasis Kearifan Lokal Di SMP N 4 Palangka Raya - Kartika Ananda; Triyani, Triyani; Suprayitno; Yuana Ledy Prilia; Huda Musthofa; Delni (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The purpose of this community service activity was to provide students with an understanding of the importance of using social media wisely in their school and outside of school life, thereby minimizing various forms of bullying, especially cyberbullying. In this community service activity, students were given an understanding of the definition and forms of cyberbullying, as well as the negative impacts of cyberbullying on victims, perpetrators, and the social environment through educational videos based on local wisdom from Central Kalimantan. The Huma Betang philosophy was used to instill character values ​​such as tolerance, unity, kinship, and mutual respect in digital interactions. This activity not only strengthened understanding of the material but also encouraged students to reflect on their individual and social behavior in the digital space. Overall, this activity successfully fostered students' awareness and commitment to being part of tackling cyberbullying in the school environment and on social media. This demonstrated that students not only understood the material but also possessed the enthusiasm to become agents of change in developing anti-cyberbullying characters.